Analisis Pengaruh Harga, Kualitas Produk, Promosi Dan Lokasi Terhadap Keputusan Pembelian Rumah (Studi Kasus Pada Pembeli Perumahan Havaland Malang) - Andre Maulana Rozikin; Agus Widarko; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the effect of price, product quality, promotion and location variables on House Purchase Decisions in Havaland Malang housing either partially or simultaneously. This type of research is quantitative research. The sampling technique used was total sampling or saturated sampling with all members of the population used as a sample of 51 consumers who bought houses in Havaland Malang housing. The regression equation in this study is multiple linear regression which is used to test the effect of the independent variables on the dependent variable. The results of hypothesis testing indicate that the price has a regression coefficient of 0.149 (á = 0.260), product quality 0.294 (á = 0.022), promotion 0.579 (á = 0.000), location -0.117 (á = 0.257) and simultaneously calculated F value (26.99) is greater than F table (2.012). Based on the calculation results, it is explained that the price and location variables have no effect on purchasing decisions, while product quality and promotions have a significant effect, simultaneously affecting purchasing decisions. Keyword: Price, Product Quality, Promotion, Location And Purchasing Decisions.